Study Time at the Coffee Shop: Exploring Student Motives through a Phenomenological Study - Gloria Winda Kurnianto; Aggacitto; Rizky Taj'Riya Ardillah (Indonesian Psychological Research, 2025)
Coffee has become a lifestyle among Indonesians, and the trend of coffee culture is growing rapidly, especially among young people. The development of coffee culture has made coffee shops not only a place to transact coffee, but also to gather, conduct meetings, and even do assignments. As one of the popular locations, coffee shops have become a favorite place for most students or workers who work from anywhere (WFA) in Indonesia. Several related studies have highlighted the attributes of the coffee shop rather than the motives of the people to go to coffee shop. Therefore, this study aims to understand the subject's motives in choosing a coffee shop as a place to work or study. This study uses a qualitative approach with a phenomenological method on visitors who work on assignments or in coffee shops with subject criteria who work on assignments or work in coffee shops at least once a week and have a status as a student. This research succeeded in revealing four significant findings, namely: 1) motive of achievement; 2) types of tasks carried out in the coffee shop; 3) Encouragement as a reinforcement of the motive of achievement; and 4) factors that influence the work carried out in the coffee shop. This research concludes that coffee shops have an essential role as an alternative place for students to study and work. By providing a conducive atmosphere, adequate facilities, and quality products, coffee shops can support students' academic productivity in completing assignments.